2020
DOI: 10.1063/1.5138672
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced hybrid improper ferroelectricity in Sr3−xBaxSn2O7 ceramics with a Ruddlesden–Popper (R–P) structure

Abstract: Hybrid improper ferroelectricity (HIF) has received increasing scientific attention since it provides great potential for realizing single phase room temperature multiferroicity with strong magnetoelectric coupling, and Ruddlesden–Popper (R–P) compounds AO(ABO3)n with even n are the most important candidates for HIFs. However, the modulation of ferroelectric polarization is recognized as a challenging issue. Here, Sr3−xBaxSn2O7 ceramics with a large remanent polarization with respect to other R–P HIFs (∼1.0 μC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 31 publications
3
16
0
Order By: Relevance
“…We apply the D-LACBED technique to the Ruddlesden-Popper phase Ca 3 Mn 2 O 7 , which has attracted interest as a multiferroic (Benedek & Fennie, 2011;Fawcett et al, 1998) with the emergence of ferroelectric-ferromagnetic coupling occurring through the coupling of two non-polar modes with different symmetries. This effect has become known as hybrid improper ferroelectricity (Benedek & Fennie, 2011) and is currently being studied in a variety of related materials (Senn et al, 2015;Bansal et al, 2019;Xu et al, 2019;Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…We apply the D-LACBED technique to the Ruddlesden-Popper phase Ca 3 Mn 2 O 7 , which has attracted interest as a multiferroic (Benedek & Fennie, 2011;Fawcett et al, 1998) with the emergence of ferroelectric-ferromagnetic coupling occurring through the coupling of two non-polar modes with different symmetries. This effect has become known as hybrid improper ferroelectricity (Benedek & Fennie, 2011) and is currently being studied in a variety of related materials (Senn et al, 2015;Bansal et al, 2019;Xu et al, 2019;Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In this letter, we show that a particular group of ferroelectrics, the A 3 Sn 2 O 7 hybrid-improper ferroelectrics (HIFs) [35][36][37][38][39] behave differently, and their structural polarization is strongly enhanced by the free electrons introduced by chemical doping or electrostatic gating. This is related to an increase in the oxygen octahedral rotation angles induced by the added electrons in the parent perovskite compounds, which in turn leads to a larger structural polarization in these layered perovskite Ruddlesden-Popper (RP) phases [40].…”
mentioning
confidence: 99%
“…While it is not always possible to order same charge cations in bulk, molecular beam epitaxy has been successfully used to obtain targeted chemical pressure in other RP phases (SrTiO 3 ) n (BaTiO 3 ) m SrO [57]. In Sr up to 10% of Ba ions are reported to preferentially substitute inequivalent Sr sites, however, the ordering tendencies depend sensitively on changes in the substitution amount [39]. We consider a structure where the 2/3 of Sr cations are substituted with Ba to form Ba 2 SrSn 2 O 7 , where the Ba cations are on the double-rocksalt layers of the RP structure, as shown in Fig.…”
mentioning
confidence: 99%
“…Curie temperatures are obtained from the DSC measurements reported previously. 12,40,43,50 The linear fitting results are depicted by red dash lines with the critical τ value [Color figure can be viewed at wileyonlinelibrary.com] there are the rather simple antiparallel 180°-type domain configurations in Ca 3 [Mn 0.5 (Fe 0.5 Nb 0.5 ) 0.5 ] 2 O 7 , and this is similar to the situation in Ca 3 Ti 2 O 7 . [43][44][45] The previous work has also demonstrated that engineering the phase transition by chemical substitution is a useful method to modulate the domain configurations in ferroelectrics.…”
Section: Resultsmentioning
confidence: 77%
“…(C) Curie temperatures of n = 2 R‐P HIFs against the tolerance factors of their perovskite units. Curie temperatures are obtained from the DSC measurements reported previously 12,40,43,50 . The linear fitting results are depicted by red dash lines with the critical τ value [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Resultsmentioning
confidence: 99%